Praktik Pengumpulan Batu Sungai dan Pengaruhnya terhadap Masyarakat Desa Taliabo - Irmayani, Irmayani; Hapsa, Hapsa; Marzuki, Muhammad; Bakari, Yulianti (SIGn Journal of Social Science, 2022)
This research aims to understand how the Taliabo Village community utilizes the potential of Sausu River rocks, identify the challenges faced by rock gatherers, and explore the socio-economic dynamics of the village in addressing these challenges. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that gathering rocks in the Sausu River of Taliabo Village is a vital economic activity supporting the livelihood of part of the community. Adapting to natural conditions and using traditional tools like tire rafts and gate-gate demonstrate the community’s resilience and creativity in utilizing local resources. Although flexible working hours offer adaptation to uncertainties, the pricing structure of rocks based on their size provides significant economic opportunities. However, challenges such as natural conditions in the dry season and health issues add difficulties to this work. Furthermore, socio-economic aspects such as the culture of mutual aid underscore the importance of communal cooperation in overcoming hardships. At the same time, limitations in meeting education and housing needs reflect broader challenges faced by the river rock gatherer community in Taliabo Village. Therefore, the Government of Parigi Moutong Regency is recommended to support the rock gathering activities in the Sausu River as an essential part of Taliabo Village’s local economy. It could include providing training and access to more efficient technology to enhance productivity and work safety for river rock gatherers. Additionally, rock gatherers are advised to adopt safer and more sustainable work practices, including ergonomic tools and attention to occupational health and safety. For the Taliabo Village community, it is recommended that the existing mutual aid system be strengthened. These joint initiatives can help address some of the socio-economic challenges the river rock gatherer community faces while strengthening communal resilience against economic and natural uncertainties.